BuShen HuoXue Decoction Promotes Decidual Stromal Cell Proliferation via the PI3K/AKT Pathway in Unexplained Recurrent Spontaneous Abortion. (5th October 2020) - Feng, Xiaoling; Jiang, Sha; Leung, WingTing; Wang, Ling; Gober, Hans Jürgen; Chen, Lu; Zhang, Yang; Wang, Ling
Abstract : BuShen HuoXue decoction (BSHXD) has been used to treat patients with unexplained recurrent spontaneous abortion (URSA). However, the chemical compounds and mechanism by which BSHXD exerts its therapeutic and systemic effects to promote the proliferation of decidual stromal cells (DSCs) has not been elucidated. This work sought to elucidate the cellular and molecular mechanism of BSHXD in terms of inflammatory factors IL-17A in DSCs in vitro because of the critical roles of inflammation, apoptosis, and immunity in the development and progression of pregnancy loss. Twelve migratory chemical compounds from BSHXD extract were qualitatively analyzed by high-performance liquid chromatography (HPLC). DSCs were collected from normal early pregnancy (NEP) and URSA to determine whether BSHXD affects IL-17A/IL17RA via the PI3K/AKT pathway. Abnormal apoptosis and activated p-AKT were observed in URSA DSCs. RhIL-17 A, LY294002 (a PI3K pathway inhibitor), and BSHXD were individually or simultaneously administered in NEP DSCs, suggesting that BSHXD restored cell proliferation without excessive stimulation and IL-17A promotes proliferation via the PI3K/AKT pathway. Using the same intervention in URSA DSCs, qRT-PCR measured the upregulated mRNA levels of IL-17 A/IL-17RA, PI3K, AKT, p-AKT, PTEN, Bcl-2, and Bcl-xL and downregulated mRNA levels of BAD and ACT1 after treatment with BSHXD. We demonstrated that BSHXD affected IL-17A/IL-17R via PI3K/AKT pathway to promote the proliferative activity of DSCs in URSA. These results provide a new insight to further clarify the relationship between inflammation and apoptosis and the mechanism of imbalance in the dynamic equilibrium between Th17/Treg immune cells at the maternal-fetal interface.